Memory and Personality Development in Adulthood: Evidence From Four Longitudinal Studies. (8th September 2020) - Stephan, Yannick; Sutin, Angelina R; Luchetti, Martina; Terracciano, Antonio
Abstract: Objectives: Personality traits have been related to concurrent memory performance. Most studies, however, have focused on personality as a predictor of memory; comparatively less is known about whether memory is related to personality development across adulthood. Using 4 samples, the present study tests whether memory level and change are related to personality change in adulthood. Method: Participants were drawn from 2 waves of the Wisconsin Longitudinal Study Graduates (WLSG; N = 3, 232, mean age = 64.28, SD = 0.65) and Wisconsin Longitudinal Study Siblings (WLSS; N = 1, 570, mean age = 63.52, SD = 6.69) samples, the Midlife in the United States (MIDUS; N = 1, 901, mean age = 55.43, SD = 10.98), and the Health and Retirement Study (HRS; N = 6, 038, mean age = 65.47, SD = 8.28). Immediate and delayed recall and the 5 major personality traits were assessed at baseline and follow-up. Results: There was heterogeneity in the associations across samples. A meta-analysis of latent change in the four samples indicated that lower baseline memory performance was related to an increase in neuroticism ( B = −0.002; 95% CI = −0.004, −0.0008) and a decrease in agreeableness ( B = 0.004; 95% CI = 0.002, 0.007) and conscientiousness ( B = 0.005; 95% CI = 0.0008, 0.010). In addition, declines in memory were related to steeper declines in extraversion ( B = 0.06; 95% CI = 0.003, 0.11), openness ( B = 0.04; 95% CI = 0.007, 0.069), and conscientiousness ( B = 0.05; 95% CI = 0.019, 0.09). Discussion: The present study indicates that poor memory and declines in memory over time are related to maladaptive personality change. These associations, however, were small and inconsistent across samples.